Analysis Of Compensation And Motivation For Job Satisfaction Of Disaster Management Agency Employees Regional (BPBD) North Sumatra Province - M. Chaerul Rizky; Nurul Rafika Husna ` (International Journal of Management, Economic and Accounting, 2023)
This study aims to determine and analyze the positive and significant effect of compensation and motivation on job satisfaction of employees of the Regional Disaster Management Agency (BPBD) of North Sumatra Province both partially and simultaneously. This study used quantitative methods with data analysis techniques used, namely multiple linear regression. The sample in this study was 53 respondents by determining the sample using saturated sampling techniques. The results showed that the compensation variable (X1) partially had a positive and significant influence on job satisfaction (Y) of employees of the Regional Disaster Management Agency of North Sumatra Province. (2) The motivation variable (X2) partially has a positive and significant influence on job satisfaction (Y) of employees of the Regional Disaster Management Agency of North Sumatra Province. (3) The variables compensation (X1) and motivation (X2) simultaneously have a positive and significant influence on job satisfaction (Y) of employees of the Regional Disaster Management Agency (BPBD) office of North Sumatra Province.